How to solve the following initial value problem:
`y''+8y'-9y=0, y(1)=1, y'(1)=0`
I think that the general solution is `y=c_1e^x + c_2e^-9x` but I could not
get the particular solution. The books' answer is
`y=1/10e^(-9(t-1)) + 9/10e^(t-1)` .
1 Answer | Add Yours
Alright, so I'll start by pointing out that this is a homogeneous second-order differential equation. Because it is homogeneous, I just wanted to point out that there is no particular solution! Don't worry about that!
Let's find the solution:
`y'' + 8y' -9y=0`
We notice that the equation is a D.E. with constant coefficients, and recall that the solution will be of the form:
` ` `y = c_1e^(lambda_1t) + c_2 e^(lambda_2t)`
where `c_1` and `c_2` are constants of integration (solved-for by using the initial conditions) and `lambda_1` and `lambda_2` being the solution to the characteristic equation.
We derive the characteristic equation by pointing out that, based on our basis function (`e^(lambdat)`) and the differential equation above that our solution is found by solving:
`lambda^2 + 8lambda - 9 = 0`
This, when solved-for, gives you `lambda = -9, 1`, So, our equation becomes exactly what you had!
`y = c_1e^x + c_2e^(-9x)`
Now, we solve for the initial conditions. We know `y(1) = 1` and `y'(1) = 0`.
We need to figure out what y' is to determine the constants:
`y' = c_1e^x -9c_2e^-9x`
So, with our initial values, we get two equations:
`1 = c_1e + c_2e^(-9)`
`0 =c_1e -9c_2e^-9`
Using the second equation, we can find an easily-substitutable expression for `c_1e`:
`c_1e = 9c_2e^-9`
So, let's substitute this into the first equation:
`1 = 9c_2e^-9 + c_2e^-9`
`1 = 10c_2e^-9`
Dividing by `10e^-9` we get our value for `c_2`:
`c_2 = 1/10 * e^9`
Now, let's solve for `c_1` by using the equation we used to substitute before:
`c_1e = 9c_2e^-9`
`c_1e = 9(1/10e^9)e^-9`
Notice that the e terms on the rigth cancel, giving us:
`c_1e = 9/10`
Dividing by e (which is the same as multiplying by `e^-1`):
`c_1 = 9/10 e^-1`
So, we have our values for `c_1` and `c_2`, and now we can find our full equation:
`y = 9/10e^-1e^x + 1/10e^9e^(-9x)`
Now, we can combine the exponents (remember `e^ae^b = e^(a+b)`)
`y = 9/10 e^(x-1) + 1/10 e^(-9x+9)`
Now, we factor out the 9 in the exponent of the right-sided term:
`y = 9/10e^(x-1) + 1/10 e^(-9(x-1))`
Now, we (just for fun times) let t = x:
`y = 9/10 e^(t-1) + 1/10e^(-9(t-1))`
And there's your answer! You had it totally correct! You just needed to stick with the problem, and you would have gotten it!
Hope that helps!
We’ve answered 319,175 questions. We can answer yours, too.Ask a question